ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN KOSMETIKA TRADISIONAL PRODUK DALAM NEGERI - Jubaedah, Lilis (Universitas Negeri Jakarta, 2014)
Abstract The purpose of this study was to determine the extent of consumer description of the general characteristics of traditional cosmetics, as well as the relationship between knowledge and attitude with consumer decision factor in the purchase of traditional cosmetics, method of data collection with questionnaires and interviews. Analysis of the data used is descriptive analytic with cross sectional approach, the number of 67 samples. Data analysis using chi square analysis and logistic regression assisted with SPSS 16 software.Results overview of consumer decisions that consumers who buy traditional cosmetics as many as 44 people (65.7%) and consumers are not buying as many as 23 people (34.3%).Based on logistic regression analysis showed no significant relationship between factors relationship with Knowledge and Attitude Factors Consumer Decision in buying traditional cosmetics. Consumers who have high knowledge level 7,130 times likely than consumers who have low knowledge level after the controlled variable attitude factor. Consumers who have a positive attitude likely to buy cosmetics 5.247 times compared to traditional consumers who have negative attitude after the controlled variable factor of knowledge. Knowledge of the most powerful variable associated with the consumer's decision to purchase traditional cosmetics is a variable factor of knowledge. Nagelkerke R2 value is 0484 which means the variability of the dependent variable that can be explained by the variability of the independent variable of 48.4%. meaning that consumers in the purchase decision variables traditional cosmetics is influenced by variable factors of knowledge and attitude factors by 48.4%, while 51.6% is influenced by other variables. Keywords; Decision consumers, traditional cosmetics, Knowledge Factor and Factor attitude. ABSTRAK Penelitian ini bertujuan untuk mengetahui sejauh mana gambaran karakteristik umum konsumen kosmetik tradisional, serta hubungan faktor pengetahuan dan faktor sikap dengan keputusan konsumen dalam membeli kosmetik tradisional, Metode pengumpulan data dilakukan dengan pengisian kuesioner dan wawancara. Analisis data yang digunakan yaitu deskriptif analitik dengan pendekatan cross sectional, dengan jumlah 67 sampel. Analisis data dengan menggunakan analisis chi square dan regresi logistik dibantu dengan software SPSS 16. Hasil Penelitian gambaran keputusan konsumen yaitu konsumen yang membeli kosmetik tradisional sebanyak 44 orang (65.7%) dan Konsumen yang tidak membeli sebanyak 23 orang (34.3%). Berdasarkan analisis regresi logistik menunjukkan ada hubungan bermakna antara hubungan Faktor Pengetahuan dan Faktor Sikap dengan Keputusan Konsumen dalam membeli kosmetik tradisional. Konsumen yang mempunyai tingkat pengetahuan tinggi berpeluang 7.130 kali dibanding konsumen yang mempunyai tingkat pengetahuan rendah setelah dikontrol variabel faktor sikap. Konsumen yang mempunyai sikap positif berpeluang membeli kosmetik tradisional 5,247 kali dibanding konsumen yang mempunyai sikap negative setelah dikontrol variabel faktor pengetahuan.Variabel pengetahuan yang paling kuat berhubungan dengan keputusan konsumen dalam membeli kosmetik tradisional adalah variabel faktor pengetahuan.Nilai Nagelkerke R2 adalah 0.484 yang berarti variabilitas variabel dependen yang dapat dijelaskan oleh variabilitas variabel independen sebesar 48.4%.artinya variabel keputusan konsumen dalam membeli kosmetik tradisional dipengaruhi oleh variabel faktor pengetahuan dan faktor sikap sebesar 48,4%, sedangkan 51,6% dipengaruhi oleh variabel lainnya. Kata Kunci: Keputusan konsumen , kosmetik tradisional, Faktor Pengetahun dan Faktor Sikap.